The Book is a Noble Teacher - Porsieva Zamira Mukhtorovna; Ismoilova Markhabo Boisarovna (Researchparks Publishing, 2021)
This article discusses the issues that need to be addressed with young people to shape the reading culture that has become a global issue today, as well as effective ways to shape the reading culture of students